METHODOLOGY FOR ORGANIZING LABORATORY CLASSES IN ATOMIC PHYSICS BASED ON AN INTEGRATED APPROACH - Khudayberdiyev E.N; Samandarov Latifbek Qalandar o’g’li (Modern American Journals, 2025)
At present, in order to address the problem of electricity shortages in our country, promising plans such as the use of nuclear power plants, wind energy, and solar energy are being developed. In these long-term plans and decisions, the use of nuclear energy is considered one of the key components, and priority tasks such as “Training personnel in the field of nuclear energy, developing educational institutions, and equipping educational-practical laboratories in nuclear physics with laboratory and instructional equipment, models, and analytical simulators” [1] have been defined. Ensuring the implementation of this resolution requires the preparation of highly qualified future physics teachers who possess modern knowledge of atomic physics and advanced teaching technologies. In the system of continuous education, along with theoretical knowledge, performing practical and laboratory work during the teaching of the physics course is essential, since students' theoretical knowledge is further strengthened through experiments and calculations during practical and laboratory activities [2].